Research on the impact of mutual elderly care on the physical and mental health of rural elderly in China - Jialiang Liu; Xiaohan Liu; Bin Hu; GuangYao Liu (Scientific Reports)
Abstract To study the impact of mutual care on the physical and mental health of rural elderly, and provide countermeasures and suggestions for the long-term development of mutual care. Data chosen from the 2018 China health and retirement longitudinal study (CHARLS) were selected, with 8369 elderly people aged ≥ 60 years old, and propensity scores were matched using nearest-neighbor matching, kernel matching, and radius matching, and then heterogeneity was used to analyze the mean effect values among different populations. The results of propensity score matching PSM showed that participation in mutual care had a significant positive effect on the mental health of the rural elderly, with a net effect of 0.020 ~ 0.027, and a significant negative effect on the physical health of the rural elderly, with a net effect of −0.029~−0.030. Heterogeneity analyses showed that participation in mutual care had no significant effect on the physical and mental health of the rural elderly who did not suffer from chronic diseases. Physical and mental health does not have a significant effect. The net effect is −0.06031 to −0.035, and the net effect is 0.029 to 0.030. The rate of rural elderly people’s participation in mutual aid is low, and participation in mutual aid has different degrees of influence on the physical and mental health of rural elderly people, different characteristics of rural elderly people’s participation in mutual aid have different degrees of influence on their physical and mental health.